If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 4 = -3 + -8x Reorder the terms: 4 + 3x = -3 + -8x Solving 4 + 3x = -3 + -8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '8x' to each side of the equation. 4 + 3x + 8x = -3 + -8x + 8x Combine like terms: 3x + 8x = 11x 4 + 11x = -3 + -8x + 8x Combine like terms: -8x + 8x = 0 4 + 11x = -3 + 0 4 + 11x = -3 Add '-4' to each side of the equation. 4 + -4 + 11x = -3 + -4 Combine like terms: 4 + -4 = 0 0 + 11x = -3 + -4 11x = -3 + -4 Combine like terms: -3 + -4 = -7 11x = -7 Divide each side by '11'. x = -0.6363636364 Simplifying x = -0.6363636364
| 8+7x=6x+3 | | k=4x^2+-12x^1 | | 16-8x=16-5x | | 4(4y-3)-(2y+3)= | | (-4/10)d=-25 | | 1/4x=2/5x | | 6xy=5 | | -0.3(x-9)=-1 | | X+7-4(x+1)=10 | | 7x+5=38+4x | | x+36/8=1/4x | | x+36/8=1/4 | | 3y-9=36 | | 8/(5-i) | | 5(7-4x)=35 | | w^2-3w+5=0 | | 50*1/20=20x*1/20 | | -3.6x=42.48 | | 5z+.12=6z+.6 | | 30=-6d | | -10+x=3x-32 | | 2(3+x)=4-3(7-x) | | 20y^2s+15y^3s^7=5y^2s | | 3x+7(X-7)=3(x-7) | | 6/5y=30 | | k/6=9 | | f(x+9)=x^2-4x-7 | | 12+2y=6 | | 45000.00-22000x=0 | | y^2-10y+23=0 | | 6y+30=3x | | x^3-x^2+7x+2=0 |